Conceptualizing Intellectual Property Laws as A Bankruptcy Property (Beodel) In Indonesian Laws: A Normative Juridical Approach - Nainggolan, Bernard (Universitas Islam Sultan Agung, 2022)
This research examines the ramifications of bankruptcy on Intellectual Property Rights (IPRs) and underscores the necessity of safeguarding asset owners' rights within the bankruptcy process. By utilizing two primary methodologies, namely the normative juridical approach and the conceptual approach, the study evaluates the legal framework governing IPRs in the context of bankruptcy. Employing a normative juridical research methodology, the study draws upon primary, secondary, and tertiary legal literature. The primary focus of this research is on the legal provisions concerning the preservation of Intellectual Property Rights amidst bankruptcy proceedings. The findings underscore the crucial role of coordination among asset owners, creditors, and the judiciary in resolving bankruptcy cases involving IPRs. Protection of these rights is paramount not only within bankruptcy contexts but also amid the broader landscape of globalization and international trade dynamics. Collaborative efforts involving governments, legal institutions, international organizations, and industry stakeholders are essential to foster growth, innovation, and uphold values of environmental sustainability and responsibility within the industry. Adequate protection of IPRs serves as a catalyst for stimulating innovation and creativity, while simultaneously ensuring environmental sustainability and promoting inclusive economic growth.